Local solvability of a constrainedgradient system of total variation - C. E. Chidume; H. Zegeye (Abstract and Applied Analysis)
Suppose X is a real q-uniformly smooth Banach space and F,K:X→X with D(K)=F(X)=X are accretive maps. Under various continuity assumptions on F and K such that 0=u+KFu has a solution, iterative methods which converge strongly to such a solution are constructed. No invertibility assumption is imposed on K and the operators K and F need not be defined on compact subsets of X. Our method of proof is of independent interest.